Implementation of Guidance for Prisoners of Motorcycle Theft in Class I Medaeng Surabaya Correctional Facility - Yeremia Novianto; Yana Indawati (Universitas Merdeka Madiun, 2024)
Abstract Introduction to the Problem: It can be seen that Crime Clearance (CC) or the number of criminal offenses resolved is smaller than Crime Total (CT) or the total number of criminal offenses that occurred, so it can be concluded that the level of crime has increased quite drastically from 2021 to 2022. Purpose/Study Objectives: This research was conducted to find out how coaching is carried out for convicts of motorcycle theft at the Medaeng Surabaya Class I Detention Center. Design/Methodology/Approach: This research is an empirical research where the analysis is carried out based on data and facts obtained from interviews and field observations regarding a legal event, in this case coaching as well as obstacles and efforts made at the Medaeng Surabaya Class I Detention Center. Findings: The coaching carried out at the Medaeng Surabaya Class I Correctional Institution is less than optimal, but the handling is in accordance with Law No. 12 of 1995 concerning Corrections, the implementation of which is regulated by Government Regulation No. 31 of 1999 concerning the Guidance and Guidance of Prisoners. Class I Medaeng Surabaya Correctional Institution officers have made repressive and preventive efforts including the application of disciplinary sanctions, improving the quality of officers, improving the quality of facilities and infrastructure and improving the quality of cooperation with other agencies. Paper Type: Research Article Keywords: Coaching; Theft; Motorcycle